Lectin‐complement pathway molecules are decreased in patients with cirrhosis and constitute the risk of bacterial infections. (28th February 2017) - Foldi, Ildiko; Tornai, Tamas; Tornai, David; Sipeki, Nora; Vitalis, Zsuzsanna; Tornai, Istvan; Dinya, Tamas; Antal‐Szalmas, Peter; Papp, Maria
Abstract: Background & Aims: Lectin pathway molecules of the complement system are synthesized by hepatocytes and have pivotal role in innate host defence against infectious organisms. Ficolins (FCNs) act as soluble pattern recognition molecules, while mannan‐binding lectin serine proteases(MASPs) do as effector molecules in elimination of pathogens. We aimed to study the significance of low level of these molecules in the development of cirrhosis‐associated bacterial infections, which has not been elucidated so far. Methods: Sera of 266 stable outpatients with cirrhosis and 160 healthy subjects were assayed for a panel of lectin molecules (FCN‐2, FCN‐3 and MASP‐2) by ELISA. In cirrhosis, a 5‐year follow‐up observational study was conducted to assess a possible association between lectin levels and development of clinically significant bacterial infections(CSI). Results: FCN‐2, FCN‐3 and MASP‐2 levels were significantly lower in cirrhosis compared to healthy subjects and decreased according to disease severity ( P <.001 for all molecules). In Kaplan‐Meier analysis, development of CSI was associated with low level of FCN‐2 (<427 ng/mL, pLogRank =0.047) and FCN‐3 (<4857 ng/mL, pLogRank =0.029), but not with MASP‐2 deficiency (<100 ng/mL, pLogRank =0.306). Combined FCN deficiency was associated with increased risk of development of bacterial infections in a step‐wise manner. Patients with low level of both FCNs had higher cumulative probability of CSI (63.8%) compared to those with low level of one or normal FCN (52.7% and 45.7%, pLogRank =0.016). Neither FCN serum profile, nor MASP‐2 deficiency were associated with infection‐related mortality. Conclusions: Low level of FCNs associated with hepatic insufficiency might be considered as an additional constituent of cirrhosis‐associated immune dysfunction.